Strategic Management of Rural Tourism Towards Gender - Sensitive Planning - Dadvar-Khani, Fazileh; Ghanian, Mansour (International Journal of Geography and Geology, 2016)
Gender blind tourism management, eventually will lead to unsustainable development. This Qualitative research has established to explore the gender needs and opinions related to tourism development, via strategic management The statistical population of this research is elite people that has been involved in tourism activities in rural areas of Kan district in the North- West of Tehran- Capital city of Iran .Two focus group including 23 men and 16 women had attended in separate workshops .The technique of SWOT had been used .The result shows there are convergence between the views of men and women about strengths of tourism. Meanwhile the divergence appears in the case of weaknesses and threat points, as that women are more concerned about environmental degradation. However, men think about physical facilities. As opportunities, men emphasis on economic prosperity, but women believe that tourism promotes them a higher social status in the family and society.